(untitled) (Jurnal Manajemen Bisnis, 2026)
Coffee is a high-value agricultural commodity in the global economy, both as a source of foreign exchange for producing countries and a global trade commodity. This study aims to examine the influence of atmosphere, price, location, and product design on consumer satisfaction at Kopi Kulo Bandar Lampung. This type of research is quantitative research. The study was conducted among all consumers in Bandar Lampung with a total of 133 respondents. The results of the study indicate that partially atmosphere and price do not have a significant effect on consumer satisfaction, and subsequently location and product design partially have a significant effect on consumer satisfaction. Simultaneously, atmosphere, price, location, and product design have a significant effect on consumer satisfaction.